Price and investment relationships : a study in applied economics - Shone, Robert Minshull (London : Elek, 1975)
It is designed for both students of management economics and businessmen concerned with issues of pricing and investment.
Includes index.
kjo 18/01/2019
Loans
Keywords: Pricing; Capital investments; Steel industry and trade